Endoscopic Management of Genitourinary Foreign Bodies - Song, Joseph B (MedReviews, LLC, 2013)
Retrieval of foreign bodies from the genitourinary system, most commonly inserted for sexual satisfaction or as a result of a psychiatric illness, can pose a significant surgical challenge. Due to their breadth of size, shape, and location within the genitourinary system, endoscopic management can be difficult. Here, we review the management of four cases of foreign object insertion into the genitourinary system and their outcomes and management.